The Academic Success Rate of Proposition 48 Student-Athletes: A Study of Student-Athletes at a Mid-western University - Judge, Larry W. (My University, 1992)
The study was designed to assess the academic requirements of NCAA Bylaw 14.3 as a predictor of student-athletes' academic success by studying three factors: (I) attrition rate; (2) cumulative grade point average; and (3) first semester grade point average. Participants in this study were 130 student-athletes enrolled at a midwestern university between August 1, 1986, and January 1, 1991. No significant differences were found regarding attrititon rates. For the first semester GPA variable there were two significant findings. Student-athletes who met the requirements had a mean GPA after one semester of 2.63, while Proposition 48 student-athletes had a mean GPA of 2.03. Black Proposition 48 student-athletes had a mean GPA after one semester of 1.81; white Proposition 48 student-athletes had a mean of 2.35. For cumulative GPAs, there were also two significant differences found. Student-athletes meeting the requirement had a mean GPA after seven semesters of 2.60, while the Proposition 48 group had a mean of 2.04. Black Proposition 48 student-athletes had a mean GPA after seven semesters of 1.91, while white Proposition 48 student-athletes had a mean of 2.25. The author recommended that initial eligibility standards be raised. The results of this study indicate that Bylaw 14.3 is grossly inequitable to black student-athletes who do not meet its requirements. "Schools continue to violate their own admissions policies by admitting star athletes who have little chance of earning a degree. The results of this study support this view." - p. 44
Keywords: eligibility; race; demographics; academic performance